ORIGIN OF ENTERIC NERVOUS SYSTEM CELLS AND MIGRATION PATHWAYS DURING EMBRYONIC DEVELOPMENT - Djuknic, Milos; Puskas, Nela; Labudovic Borovic, Milica; Jankovic, Radmila (HEALTH CARE, 2022)
The enteric nervous system (ENS) is represented by a complex network of neurons, glial and other cells within the wall of the digestive tract. ENS is responsible for numerous, vital functions in our body. Thus, ENS regulates motility of the digestive tract, secretion into the intestinal lumen, exchange of fluid and electrolytes through the mucosa, as well as mucosal perfusion. In order to perform these important functions, proper embryonic development of ENS is necessary. ENS cells are derived from precursor cells of the neural crest (NCCs – neural crest cells). Two cell populations that contribute to the largest number of future ENS cells are the vagal and sacral NCCs. Vagal NCCs enter the primitive gut tube in the region of the future esophagus (foregut), and begin their migration, through the midgut towards the hindgut and the future anal region. Sacral NCCs enter the hindgut region following the extrinsic nerve fibers and continue their migration rostrally, towards vagal NCCs. Along with the migration process, these cells undergo other important processes, such as proliferation, neuro-glial differentiation, gangliogenesis, axonal pathway formation and synaptogenesis. All these processes are strictly regulated by numerous signaling pathways, which are still being actively researched. Modern lineage tracing and other technologies, that enabledfollowing of individual precursor cells through their development pathways, will significantly contribute to the better understanding of development of ENS. This may have repercussions in improving the diagnosis and treatment of some developmental (Hirschsprung disease) and other ENS disorders.
Keywords: enteric nervous system, embryonic development, cell migration, Hirschsprung disease